The good widow : a novel - Fenton, Liz; Steinke, Lisa (Lake Union Publishing, 2017)
Elementary school teacher Jacqueline Jacks Morales's marriage was far from perfect, but even in its ups and downs it was predictable. Familiar. Or at least she thought it was, until two police officers showed up at her door with devastating news. Her husband of eight years, the one who should have been on a business trip to Kansas, had suffered a fatal car accident in Hawaii. And he wasn't alone.